Evidence for cleavage of lignin by a brown rot basidiomycete - Daniel J. Yelle; John Ralph; Fachuang Lu; Kenneth E. Hammel (Environmental Microbiology, 2008)
Summary Biodegradation by brown‐rot fungi is quantitatively one of the most important fates of lignocellulose in nature. It has long been thought that these basidiomycetes do not degrade lignin significantly, and that their activities on this abundant aromatic biopolymer are limited to minor oxidative modifications. Here we have applied a new technique for the complete solubilization of lignocellulose to show, by one‐bond 1 H‐ 13 C correlation nuclear magnetic resonance spectroscopy, that brown rot of spruce wood by Gloeophyllum trabeum resulted in a marked, non‐selective depletion of all intermonomer side‐chain linkages in the lignin. The resulting polymer retained most of its original aromatic residues and was probably interconnected by new linkages that lack hydrogens and are consequently invisible in one‐bond 1 H‐ 13 C correlation spectra. Additional work is needed to characterize these linkages, but it is already clear that the aromatic polymer remaining after extensive brown rot is no longer recognizable as lignin.